An integrative approach using DNA barcode and scanning electron microscopy for the effective identification of sympatric species of the genus Farfantepenaeus Burukovsky, 1997 - França, Nielson F.C.; Moraes, Alex B.; Carvalho-Batista, Abner [UNESP]; Melo, Marília C.R.B.; Zara, Fernando J. [UNESP]; Mantelatto, Fernando L.; Freire, Fúlvio A.M. (Elsevier, 2021)
Farfantepenaeus subtilis, F. isabelae, and F. brasiliensis occur in sympatry along the northern coast of Brazil, up to the state of Rio Grande do Norte. The species of Farfantepenaeus are highly similar and new approaches are needed to better distinguish them. Here, we combined molecular and morphological analysis including scanning electron microscopy for more efficient identification and differentiation of these three species. The molecular analysis confirmed the efficacy of the set of diagnostic characters currently available for the species. The morphological analyses led to the definition of a new dichotomous character between F. subtilis and F. isabelae and uncovered other differences, which furnished new data to the formulation of an updated diagnosis of the target species. Our results contribute to more effective identification of these species, serving as a baseline for the adequacy of fishing management practices throughout their area of occurrence and for future studies on systematics and ecology.
Keywords: COI; Penaeids; Pink shrimp; Systematics and taxonomy